2016
DOI: 10.15406/jnmr.2016.03.00058
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic Analysis for Livers from Sprague-Daley Rats Following 12-Week Inhalation Exposure to Silver Nanoparticles

Abstract: Silver nanoparticles (AgNPs) have been extensively applied to many industrial and biomedical fields due to their antibacterial effect. However, a large number of applications is also lead to health and environmental safety concerns. Up to date, it was well-known that AgNPs induced reactive oxygen species (ROS) production, cytotoxicity, pro-inflammatory effect, DNA damage, cell cycle disturb, necrosis and apoptosis by many researches. Also, several studies have been performed to investigate the microarray test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…A similar trend was found in another study investigating the relationship between T2D and insulin resistance and exposure to vehicle emissions (Table 7); a significant relationship between exposure and T2D prevalence was only found in women (Brook et al, 2008). PM 2.5 toxicity may overlap mechanistically with Ag NPs where upregulation of genes related to diabetes has been observed in the livers of rats (Kim et al, 2016;Table 2). However, rodent studies only revealed an association of Ag Np inhalation and T2D in male animals, as opposed to the results of human PM 2.5 studies, which suggest that women are more susceptible than men.…”
Section: Pm 25supporting
confidence: 80%
See 2 more Smart Citations
“…A similar trend was found in another study investigating the relationship between T2D and insulin resistance and exposure to vehicle emissions (Table 7); a significant relationship between exposure and T2D prevalence was only found in women (Brook et al, 2008). PM 2.5 toxicity may overlap mechanistically with Ag NPs where upregulation of genes related to diabetes has been observed in the livers of rats (Kim et al, 2016;Table 2). However, rodent studies only revealed an association of Ag Np inhalation and T2D in male animals, as opposed to the results of human PM 2.5 studies, which suggest that women are more susceptible than men.…”
Section: Pm 25supporting
confidence: 80%
“…No sex-differences in hepatic Ag NP accumulation was observed. Both male and female rats had increased metabolism-related gene expression in the liver, but only males upregulated genes involved with xenobiotic metabolism in the kidneys (Kim et al, 2016), which may explain differences in renal clearance and accumulation observed in other studies. In contrast to accumulation data, Sung et al (2009) showed that Ag NP-treated male animals had a greater decrease in kidney function, as indicated by tubular basophilia and urine protein, compared to females.…”
Section: Silver and Gold Npsmentioning
confidence: 71%
See 1 more Smart Citation